Detection and Management of Myocarditis and Fulminant Myocarditis - Siti Elkana Nauli; Hawani Sasmaya Prameswari (Jurnal Kardiologi Indonesia, 2020)
Myocarditis is commonly caused due to systemic viral infection with cardiotropic nature. In the acute phase, this disorder could cause lethal hemodynamic or arrhythmic disorders. Newest studies showed that the use of guideline-directed medical care in the care of myocarditis will lead to better outcomes. This condition varies in presentation ranging from mild to life-threatening such as cardiogenic shock. With the current advances in early detection and circulatory support using extracorporeal membrane oxygenation (ECMO), myocarditis could be managed very well. Cases of myocarditis related to COVID 19 has been reported, however as per this time there has no confirmed pathological evidence regarding direct causation between COVID19 and myocarditis, however, in these severely ill patients, elevations in cardiac biomarkers (cTn, BNP and NTproBNP) occurs, and the administration of immunosuppressant could increase the chance of remission. Keyword: Myocarditis, fulminant, COVID 19.